Single-particle selection and alignment with heavy atom cluster-antibody conjugates - Jensen, Grant J. (The National Academy of Sciences, 1998)
A method is proposed for selecting and aligning images of single biological particles to obtain high-resolution structural information by cryoelectron microscopy. The particles will be labeled with multiple heavy atom clusters to permit the precise determination of particle locations and relative orientations even when imaged close to focus with a low electron dose, conditions optimal for recording high-resolution detail. Heavy atom clusters should also allow selection of images free from many kinds of defects, including specimen movement and particle inhomogeneity. Heavy atom clusters may be introduced in a general way by the construction of “adaptor” molecules based on single-chain Fv antibody fragments, consisting of a constant framework region engineered for optimal cluster binding and a variable antigen binding region selected for a specific target. The success of the method depends on the mobility of the heavy atom cluster on the particle, on the precision to which clusters can be located in an image, and on the sufficiency of cluster projections alone to orient and select particles for averaging. The necessary computational algorithms were developed and implemented in simulations that address the feasibility of the method.